Reliable molecular identification of nine tropical whitefly species - Ovalle Rivera, Tatiana M.; Parsa, Soroush; Hernández M., María del Pilar; Becerra López Lavelle, Luis Augusto (Wiley, 2014)
The identification of whitefly species in adult stage is problematic. Morphological differentiation of pupae is one of the better methods for determining identity of species, but it may vary depending on the host plant on which they develop which can lead to misidentifications and erroneous naming of new species. Polymerase chain reaction (PCR) fragment amplified from the mitochondrial cytochrome oxidase I (COI) gene is often used for mitochondrial haplotype identification that can be associated with specific species. Our objective was to compare morphometric traits against DNA barcode sequences to develop and implement a diagnostic molecular kit based on a RFLP‐PCR method using the COI gene for the rapid identification of whiteflies. This study will allow for the rapid diagnosis of the diverse community of whiteflies attacking plants of economic interest in Colombia. It also provides access to the COI sequence that can be used to develop predator conservation techniques by establishing which predators have a trophic linkage with the focal whitefly pest species.